Cashing in on Spinners: Revenue Estimates of Wild Dolphin-Swim Tourism in the Hawaiian Islands - Wiener, Carlie; Bejder, Lars; Johnston, David; Fawcett, Leesa; Wilkinson, Paul (Frontiers in Marine Science, 2020)
Wild dolphin-swim tourism has grown in specific locations where Hawaiian spinner dolphins (Stenella longirostris) have known resting habitat. The increased growth in dolphin-swim businesses has created an industry in Hawaii that earns an estimated $102 million (USD) annually in 2013. Semi-structured interviews with business owners, market research, and boat-based observations provide a platform for estimating revenue generated from dolphin tourism in two popular locations, Waianae, Oahu and Kailua-Kona, Hawaii Island. A revenue analysis of dolphin-swim tourism is presented using a peak season and utilization rate model. These predictions offer an accountability exercise based on a series of assumptions regarding wild dolphin-swim demand and an annual estimate of the number of viewing participants and revenue earned. The results show that dolphin viewing companies are making a larger profit than dolphin-swim businesses by approximately $19 million (USD) per year, however, both avenues are generating large earnings. Sizable differences between businesses in Kona and Waianae are discussed. The average lifetime revenue generated by a dolphin in 2013 is estimated at $3,364,316 (USD) for Waianae and $1,608,882 (USD) for Kona, and is presented as a first step in scenario analysis for policy makers looking to implement management in the bays where tourism occurs. This study offers the first revenue estimates of spinner dolphin tourism in Hawaii, which can provide context for further discussion on the impact and economic role of the dolphin-swim industry in the state.